Elemental composition of ferromanganese crusts from the Hawaiian Archipelago - James D Craig; John E Andrews; Maurice A Meylan (PANGAEA, 2022)
The paper presents the results of studies of ferromanganese deposits in the Hawaiian Archipelago. The chemical composition of ferromanganese oxide crusts and their associated substrates was determined by two methods. Atomic absorption spectrophotometry was used for the analysis of Fe, Mn, Co, Cu, Ni and AI, and Ti was determined by X-ray fluorescence using Energy Dispersive Analysis of X-rays (EDAX). Sample preparation and analytical procedures have been described in detail by Frank et al., 1976 (see related to: reference). The results of replicate analyses and the comparison to the Marine Standard Nodule (GRLD-126) (NSF-IDOE Manganese Nodule Project, unpubl, data) indicate that both precision and accuracy are in the range of 5-10% for each element.